2001
DOI: 10.1002/bit.1102
|View full text |Cite
|
Sign up to set email alerts
|

Process monitoring of an industrial fed‐batch fermentation

Abstract: Market demand places great emphasis in industry on product quality. Consequently, process monitoring and control have become important aspects of systems engineering. In this article we detail the results of a 2-year study focusing on the development of a condition monitoring system for a fed-batch fermentation system operated by Biochemie Gmbh in Austria. We also demonstrate the suitability and limitations of current state of the art technologies in this field and suggest novel modifications and configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(70 citation statements)
references
References 32 publications
0
66
0
3
Order By: Relevance
“…Since then other researchers have adopted the approach and applied it to a variety of processes. For example, Gallagher et al (1996) applied the technique to monitor nuclear waste storage vessels and Lennox et al (2001) and Lakshminarayanan et al (1996) investigated the detection of faults in fed-batch fermentation processes.…”
Section: Multiway Partial Least Squaresmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then other researchers have adopted the approach and applied it to a variety of processes. For example, Gallagher et al (1996) applied the technique to monitor nuclear waste storage vessels and Lennox et al (2001) and Lakshminarayanan et al (1996) investigated the detection of faults in fed-batch fermentation processes.…”
Section: Multiway Partial Least Squaresmentioning
confidence: 99%
“…The prediction of future process values is referred to as filling up the array. Of the three methods that were suggested by Nomikos and MacGregor (1994) for filling up the array, Lennox et al (2001) found that the most appropriate method for an industrial fed-batch process was to assume that the values of all process measurements remain at their current offset from the mean trajectory through to the end of the batch. Whilst the most suitable filling up method is likely to be process dependent, this method was also found to be the most appropriate in this work.…”
Section: Figure 1 Unfoldingmentioning
confidence: 99%
“…Batch data consist of batch runs, variables, and time, contrary to the continuous processes where only time and variables are involved. Multiway PCA has also been subject to some application studies [17]. The fact that multiway PCA was a fixed model monitoring technique and thus might lead to false alarms when it was used to monitor real processes whose normal operation involved slow changes, led Lee et al [9] to a consecutively updated multiway PCA.…”
Section: Introductionmentioning
confidence: 98%
“…These methods integrate the time-lagged windows of the process dynamic behavior with PCA and PLS respectively for on-line batch monitoring. Of the methods mentioned above, the application of MPCA to industrial batch monitoring has received the greatest attention (Gallagher and Wise, 1996;Kosanovich et al, 1996;Nomikos, 1996;Gregersen and Jorgensen, 1999;Tates et al, 1999;Westerhuis et al, 1999;Wise et al, 1999;Lennox et al, 2001).…”
Section: Introductionmentioning
confidence: 99%